Teori Belajar Humanistik dalam Pembelajaran Matematika SD - Nuraini Alkhasanah; Sri Wahyuni; Endang Fauziati (LPPM Press, 2022)
This article is a literature review on humanistic learning theory in elementary mathematics learning. The concept of learning that is carried out by humanism is to humanize humans, and emphasizes the process rather than the learning outcomes. Humanistic theory is basically a learning concept that provides an explanation of how to humanize students and actualize all the potential abilities of each student to deal with changes in the surrounding environment. This theory assumes that learning will be meaningless if there is coercion in it. This study discusses: (1) what is humanistic learning theory? (2) What is elementary mathematics learning? (3) How is elementary mathematics learning based on humanistic learning theory?